THE NEED TO USE AN INTEGRATIVE APPROACH IN THE PROCESS OF ORGANIZING TEACHING IN MEDICAL UNIVERSITIES - Mukhamedova Ozoda Akhtamovna (Bright Mind Publishing, 2026)
The article examines the issues of organizing training using an integrative approach, which assumes the integrity and systematicity of the learning process and allows for the consideration of existing interdisciplinary and intradisciplinary connections. The article provides a rationale for the need to use an integrative approach in the process of organizing teaching at a medical university, due to the fact that one of the main tasks of medical education is the formation of clinical thinking, which is impossible without understanding the unity of the material world, the interconnection and interdependence of all phenomena, facts and processes. The possibilities of the discipline "Latin language" in the implementation of the principle of integration in the organization of education in a medical university described.
Keywords: Integrative approach, competent specialists, organization of professional training, medical terminology, society.